Some remarks to recent papers on traffic analysis or the case for public Wiki-like platforms for commenting published papers. - Ricciato, Fabio
In this informal contribution we raise a few remarks and requests for clarification about some recent papers in the field of traffic analysis. These examples are illustrative of the kind of issues and open points that are encountered when reading, applying and working with published papers. The readers and followers of each published paper - especially of the best ones - form naturally a small community of interest. In most cases remarks and open points about the paper are of interest for the them all. Based on these considerations we raise the following proposal to the research community: let each conference and/or journal editor maintain an open public wiki-like commenting platform for publishing comments and rebuttals after the paper publication.
Keywords: Computer systems organization; Computer communication networks; Network operations; Network monitoring; Information systems; Information storage and retrieval; Online information services; Web based services; Documentation; Measurement